Caracterização dos compostos bioativos presentes em cascas de café da espécie coffea arabica - Laís Brito Cangussu (2017)
The objective of this work was the chemical characteristics of the bioactive compounds present in coffee husks of the Arabica species, as well as the influence of bleaching on the preservation of these compounds. The quantification of extractable and non-extractable phenolic compounds was carried out by the Folin-Ciocalteu Assay, the extractable proanthocyanidins (EPA) and non-extractable proanthocyanidins (NEPA) by a spectrophotometric method and trigonelin and caffeine by high performance liquid chromatography (HPLC). The identification of the phenolic compounds was also carried out by HPLC and the determination of the monosaccharides composition of the polysaccharides by gas chromatography. All samples presented high contents of phenolic compounds (> 500mg EAG/100 g), and bleaching contributed to the preservation of non-extractable phenolics, but caused the loss of extractable phenolics. The values of EPA and NEPA determined for all samples were higher than the values found in the literature for apple, peach and nectarine. With the results obtained, it can be stated that more than half of the caffeine and trigonelin contents of the coffee fruit are in the husks and that bleaching contributed significantly to the losses of these compounds. The phenolic compounds identified in the samples were chlorogenic acids and protocatechuic acid. Bleaching of the husks preserved fairly the chlorogenic acids and caused losses of the protocatechuic acid in the samples. The monosaccharides present in the samples were similar to those found in spent coffee grounds, except for the presence of xylose, which indicates the presence of xylans and xyloglucans in coffee husks. With the results here in obtained, it is concluded that coffee husks have a significant potential as a source of bioactive compounds and can be thus proposed for use in several applications in the food sector.